Pengaruh Pemberian Ankle Strategy Exrcise terhadap Peningkatan Keseimbangan Dinamis pada Lansia - Helena, Albherta Glory; Haryatno, Pajar; Kurniawati, Dwi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Elderly is someone who has reached the age of 60 years and over. The aging process is a process that occurs in every person and cannot be avoided, where in the aging process itself there will be a decrease in anatomical and physiological functions such as a decrease in musculoskeletal function, a decrease in cardiovascular, respiratory and nervous system function. A decrease in these body systems will have an impact on the level of dynamic balance in the elderly, causing instability or balance disorders. With these problems, the risk of falls in the elderly will be higher.Objective: to determine the effect of Ankle Strategy Exercise on improvement of dynamic balance in the elderly. Method: This research uses a true-experimental one group pre and post test design with control method.Subjects: elderly in Timang Wetan, Wonokerto, Wonogiri, totaling 30 elderly subjects, of which 15 subjects were in the intervention group and 15 other subjects were in the control group.Each research subject underwent a balance test and measurements using the Time Up and Go Test (TUG Test) at the beginning before being given treatment and after being given treatment at the end of the study.Results: The pretest and post-test difference test using paired t-test showed the result p = 0 (p < 0.5) which means there is a change or influence.Conclusion: ankle strategy exercise has an effect on improving the dynamic balance of the elderly. Keywords: Ankle strategy exercise, Dynamic Balance, Elderly, Time Up and Go Test (TUG Test).